Antibacterial Effect of Copper on Microorganisms Isolated from Bovine Mastitis - Reyes-Jara, Angelica; Cordero, Ninoska; Aguirre, Juan; Troncoso, Miriam; Figueroa, Guillermo (Frontiers in Microbiology, 2016)
The antimicrobial properties of copper have been recognized for several years; applying these properties to the prevention of diseases such as bovine mastitis is a new area of research. The aim of the present study was to evaluate in vitro the antimicrobial activity of copper on bacteria isolated from subclinical and clinical mastitis milk samples from two regions in Chile. A total of 327 microorganisms were recovered between March and September 2013, with different prevalence by sample origin (25% and 75% from the central and southern regions of Chile, respectively). In the central region, E. coli and coagulase negative Staphylococci (CNS) were the most frequently detected in clinical mastitis cases (33%), while in the southern region S. uberis, S. aureus and CNS were detected with frequencies of 22%, 21% and 18%, respectively. Antibiotic susceptibility studies revealed that 34% of isolates were resistant to one or more antibiotics and the resistance profile was different between bacterial species and origins of isolation of the bacteria. The minimum inhibitory concentration of copper (MIC-Cu) was evaluated in all the isolates; results revealed that a concentration as low as 250 ppm copper was able to inhibit the great majority of microorganisms analyzed (65% of isolates). The remaining isolates showed a MIC-Cu between 375 and 700 ppm copper, and no growth was observed at 1000 ppm. A linear relationship was found between the logarithm of viable bacteria number and time of contact with copper. With the application of the same concentration of copper (250 ppm), CNS showed the highest tolerance to copper, followed by S. uberis and S. aureus; the least resistant was E.coli. Based on these in vitro results, copper preparations could represent a good alternative to dipping solutions, aimed at preventing the presence and multiplication of potentially pathogenic microorganisms involved in bovine mastitis disease.